2016
DOI: 10.1021/acs.jpca.6b08463
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Density Functional Theoretical Investigation of Photoinduced Excited-State Intramolecular Dual Proton Transfer in Diformyl Dipyrromethanes

Abstract: In recent research [ Chem. Commun. 2014 , 50 , 8667 ], it was found that photoinduced enolization occurred in 1,9-diformyl-5,5-diaryldipyrromethane (DA) by excited-state dual proton transfer resulting in a red-shifted absorption, a phenomena not observed in 1,9-diformyl-5,5-dimethyldipyrromethane (DM) and 1,9-diformyl-5-aryldipyrromethane (MA). The observation was supported by preliminary density functional theoretical (DFT) calculations. In the work reported here, a detailed and systematic study was undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…34−41 Pradhan et al reported the TDDFT calculations of the mechanistic excited state dual PT via enolization of diformyl-dipyrromethanes through a stepwise process influenced by the substituents. 35 Another TDDFT calculation from Zhao et al revealed that the excited state double-PT mechanism of pigment alkannin involved a stepwise process, where a polar aprotic solvent affected the first PT step. 36 We have been interested in the chemistry of "buckybowls", which are curved aromatic compounds comprising fullerene fragments, and their heteroatom-doped derivatives.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34−41 Pradhan et al reported the TDDFT calculations of the mechanistic excited state dual PT via enolization of diformyl-dipyrromethanes through a stepwise process influenced by the substituents. 35 Another TDDFT calculation from Zhao et al revealed that the excited state double-PT mechanism of pigment alkannin involved a stepwise process, where a polar aprotic solvent affected the first PT step. 36 We have been interested in the chemistry of "buckybowls", which are curved aromatic compounds comprising fullerene fragments, and their heteroatom-doped derivatives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, ESIPT is quite a susceptible process, highly dependent on the external conditions such as the solvents and temperature, as well as the intrinsic natures of the compounds including the strength of the hydrogen bond. In particular, the ESIPT in the solid and the solution states are different, so that the comprehensive computational study is highly demanded for the effective design of ESIPT molecules. ,,, Time-dependent density functional theory (TDDFT) is a suitable computational method for more in-depth understanding of the mechanistic detail and electronic effect of the ESIPT process. , Recently, the mechanistic details and electronic effects of multiple excited PT process by TDDFT were highly studied. Nevertheless, reports on the intramolecular dynamic processes are still few. Pradhan et al reported the TDDFT calculations of the mechanistic excited state dual PT via enolization of diformyl-dipyrromethanes through a stepwise process influenced by the substituents . Another TDDFT calculation from Zhao et al revealed that the excited state double-PT mechanism of pigment alkannin involved a stepwise process, where a polar aprotic solvent affected the first PT step …”
Section: Introductionmentioning
confidence: 99%
“…The two reported classical photoinduced keto–enol tautomerism reactions are excited-state intramolecular proton transfer (ESIPT, Scheme A) and photoenolization , (Scheme B). The occurrence of ESIPT requires the assistance of an intramolecular hydrogen bond, and photoenolization also involves a spatially adjacent proton donor and proton acceptor. However, the proton transfers in these two types of photoreactions are reversible cyclic processes, and the ketone and enol forms cannot be separated due to the ultrafast time scale in their tautomeric equilibrium. Exploration of the photoinduced irreversible intramolecular proton transfer between the ketone and enol that produces thermally stable and isolable products is a fascinating task.…”
mentioning
confidence: 99%
“…It is particularly prevalent when water is used as the solvent, in order to consider the hydrogen bonding or coordination interactions between the probe and water molecules. In some studies, probe–solvent or analyte–solvent interactions have been investigated by including a few discrete solvent molecules . Furthermore, a hybrid quantum mechanics/molecular mechanics (QM/MM) approach has also been used to describe probe–analyte–solvent systems, whereby the probe or probe–analyte complex is treated by QM and the solvent is treated by MM.…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, probe-solvent or analyte-solvent interactions have been investigated by including a few discrete solvent molecules. 87 Furthermore, a hybrid quantum mechanics/molecular mechanics (QM/MM) approach has also been used to describe probe-analyte-solvent systems, 43,79,88 whereby the probe or probe-analyte complex is treated by QM and the solvent is treated by MM.…”
Section: Tddft Calculationsmentioning
confidence: 99%